$\newcommand{\bra}[1]{\left<#1\right|} \newcommand{\ket}[1]{\left|#1\right>}$Here is what I tried:

Given that we have two projectors: $$ A = \sum_i \ket{i} \bra{i}, \hspace{2em} B = \sum_j \ket{j} \bra{j} $$ The goal is to prove that: $$ A \otimes B = \sum_k \ket{k} \bra{k}. \tag1\label1 $$ Plugging into \eqref{1}, we get: $$ A \otimes B = \left( \sum_i \ket{i} \bra{i} \right) \otimes \left( \sum_j \ket{j} \bra{j} \right) = \sum_{i,j} \ket{i} \bra{i} \otimes \ket{j} \bra{j} \tag{2}\label{2} $$ I'm not sure how to proceed from \eqref{2}. It would be convenient if for every $\ket{i}$ and $\ket{j}$ there is a $\ket{k}$ for which the following identity is true: $$ \ket{k} \bra{k} = \ket{i} \bra{i} \otimes \ket{j} \bra{j} \tag{3}\label{3} $$ This would prove \eqref{1} immediately. Is \eqref{3} true though? If yes, why? If not, how else can we proceed to prove \eqref{1}?

  • 2
    $\begingroup$ it's just a redefinition. More precisely you should write $|k\rangle=|i,j\rangle$. The only identity you are using is $|i\rangle\!\langle i|\otimes\lvert j\rangle\!\langle j\rvert=\lvert i,j\rangle\!\langle i,j\rvert$ $\endgroup$
    – glS
    Aug 28, 2020 at 22:35
  • $\begingroup$ Thanks, that answers my question. I tried proving $|i\rangle\!\langle i|\otimes\lvert j\rangle\!\langle j\rvert=\lvert i,j\rangle\!\langle i,j\rvert$ and managed to convince myself of its truth by expanding the terms into matrices/vectors and see what gets multiplied by what, but I'm wondering if there's a "nicer" way to do this. I tried looking at the definitions in Nielsen & Chuang (10th edition) page 73 but couldn't find anything useful, which is weird because the book usually introduces the necessary identities prior to the exercises. $\endgroup$
    – Attila Kun
    Aug 29, 2020 at 3:20

1 Answer 1


I wouldn't approach the problem the way that you have. Instead, I'd take the definition of what it means to be a projector: $P$ is a projector if and only if $P^2=P$ and $P=P^\dagger$.

So, let's take $$ P=P_A\otimes P_B. $$ We can calculate $P^\dagger=P_A^\dagger\otimes P_B^\dagger=P_A\otimes P_B=P$, which follows from the assumption that $P_A$ and $P_B$ are projectors.

Similarly, $$ P^2=P_A^2\otimes P_B^2=P_A\otimes P_B=P. $$ You're done!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.